Engagement : transforming difficult relationships at work - Bolman, Lee G.; Gallos, Joan V. (Wiley, 2016)
"Master the interpersonal side of management to enhance productivity and boost success Engagement is the manager's essential primer for dealing with difficult people and managing your team. Bestselling authors Lee G. Bolman and Joan V. Gallos are back with an engaging business novella that relates real, practical techniques captured in the 4-step SURE model for handling people problems. The story centers around a manager in a new job, and her experiences applying the four steps in leading her new team. Brief interludes punctuate the story throughout to provide room for reflection, and to explain the complex interpersonal dynamics at play in commonly encountered situations. Key lessons are underscored as the foundation for a sound people strategy, and the features and details of each rule are laid out in a clear, concise manner. You'll learn alongside the story's manager as she uses the model to find artful solutions to problems that could have easily derailed her chances of success. People are the hardest part of a manger's job. No matter how well-matched their skill sets, there is always the potential for interpersonal conflicts and strains to throw the team off-course. This book shows you deft strategies for addressing those challenges with a well thought-out framework for getting your team fully invested in the group's success. Find creative solutions to persistent issues Dig into the interpersonal dynamics at work Learn how to handle--and manage--difficult people Apply key strategies for engaging the team This compact, easy-to-apply set of guidelines draws on your leadership skills while providing a strong foundation for a new managerial approach. Effective management is frequently a tightrope between results and morale, and Engagement shows you how to find your balance and steady your team"--